Pemodelan Matematika Aliran Darah Pada Arteri Perifer Akibat Pemasangan Stent - Theriq Azis Al Husein; Arif Fatahillah; Susi Setiawani (Saintifika, 2020)
Peripheral arterial disease is a disease that occurs due to narrowing of peripheral arteries caused by plaque buildup. If left too long, this disease can cause pain in the limbs and even have to be amputated. One way to treat PAP is by performing stenting or better known as angioplasty. Angioplasty is performed with the aim of opening the narrowed blood vessels so that blood flow can be normal again. Mathematical modeling is a science that can be used to simulate problems in the real world into mathematical models. Mathematical modeling can form a model that describes the state of blood flow in the peripheral arteries in accordance with the conditions and important factors in it. In this study a mathematical model of blood flow was built in the peripheral arteries to determine the effectiveness of stent placement obtained from the momentum equation and solved using the finite element method.